Дослідження гострої токсичності похідних 1,2,4-тріазолу, що містять в своєму складі ядро 1Н-тетразолу - Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович (My University, 2019)
The design of new drugs is a rather complex and multi-stage process. The modeling and creation of new biologically active compounds are one of the stages of this operation. One of the important stages of preclinical trials is the study of acute toxicity of newly synthesized compounds. Great interest in this branch is nitrogen-containing heterocycles, namely 1,2,4-triazole and their derivatives. Therefore, the purpose of our work is to study acute toxicity among new derivatives of 5-(1H-tetrazole-1-yl)-4-R-3-thio(amino)-1,2,4-triazole. The study of acute toxicity was carried out by the method of V. B. Prozorovsky on the white nonlinear rats. As a result of the experiments, acute toxicity of the 41 synthesized compounds was determined. The value of the LD50 of new derivatives of 5-(1H-tetrazole-1-yl)-4-R-3-thio(amino)-1,2,4-triazole is in the range of 357-1060 mg/kg, and according to the classification of Sidorov I. K. belong to IV and V toxicity classes.
Keywords: 1,2,4-triazole; 1Н-tetrazole; acute toxicity